Sigma metrics as quality indicators in guiding and tracking laboratory process improvement - Sengupta, Sohini; Chung, Douglas W.; Kumar, Ramdhir; Gupta, Paritosh; Upadhyay, Sonu; Rattan, Ashok (International Journal of Research in Medical Sciences, 2023)
Background: To demonstrate the utility of sigma metrics towards assessing the quality of processes, and optimization of statistical quality control rules in a high-volume clinical laboratory, in a two-phase quality improvement project. Methods: In the “pre” period, the sigma score was assessed across 25 routine high-volume assay parameters in our laboratory, comprising of 20 clinical chemistry and 5 immunoassay methods. Measures were taken to improve the analytical quality of low sigma score parameters within a 6-month period. Another sigma metric analysis was then performed in the “post” period to examine any measurable improvement. Results: The average sigma metric increased from 6.4σ to 9.2σ. Out of 25 analytes, 17 showed a significant improvement, defined as an increase in the sigma metric by greater than 1.0. Conclusions: The changes in sigma metric had a significant positive impact on the DPMO and reinforced the reliability of our test results. It showed that our quality control processes can be streamlined and simplified further, to optimize the frequency of internal quality control, while still maintaining the same level of error detection and analytical quality assurance. The analysis also provided additional benefits of achieving lesser errors, fewer sample reruns and troubleshooting, and improved turnaround time, for better clinician and patient satisfaction.